Systematic evaluation of a flat-heat-pipe-based thermal management: Cell-to-cell variations and battery ageing. (25th June 2021) - Liang, Z.; Wang, R.; Malt, A. Howard; Souri, M.; Esfahani, M.N.; Jabbari, M.
Highlights: Electrical-thermal modelling of lithium-ion battery pack. Using probability distributions of electrical resistances of cells. Inefficient cooling capacity of flat heat pipe for high tolerance cells. Inefficient cooling capacity of flat heat pipe for aged cells. Abstract: For Lithium-ion batteries, the high temperature and the high cell-to-cell temperature difference accelerates battery ageing and typically causes thermal runaway. Such temperature difference can be imposed by different parameters (such as internal resistance and polarization resistance) of every cell, so-called cell-to-cell variations. A 168-cell battery pack cooled by a flat-heat-pipe battery thermal management (BTM) method under 5C discharging rate is studied in this work. A statistical benchmark study is carried out on the cell-to-cell variations of new and aged battery packs using probability distributions. The electrical and thermal behaviours of cells were simulated using an electrical model (Simulink) and a heat transfer model (Ansys-Fluent). Results demonstrate that either of the high tolerance level and battery ageing can lead to both high local cell temperature and significant temperature difference in a battery pack. Such adverse effects may lead to the failure of heat pipe (HP) cooling. The flat-heat-pipe-based BTM method with a heat transfer coefficient of 500–2000 W / K . m 2 is successful in constraining temperature and temperature difference of a battery pack under 50 °C and 5 °C respectively.